ANALISIS KINERJA KEUANGAN PERUSAHAAN PT. BUKIT ASAM (PERSERO) TBK TANJUNG ENIM TAHUN 2015-2019 - Louis , Wilson; Sutjiati, Rosemarie (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2022)
This research was conducted to determine PT. Bukit Asam Tbk. Tanjung Enim financial performance from 2015 to 2019 using financial ratio analysis. The company’s financial ratio will be viewed from many sides using several ratios such as liquidity, profitability, solvability, activity and market ratio. Method that’s used for this research is descriptive method and data collecting method that’s used is documentation of the company’s financial performance from 2015-2019 periods. The analysis result shows that for financial performance of PT. Bukit Asam Tbk. Tanjung Enim indicates good profitability, liquidity, solvency ratios as well as good market ratios, while the activity ratios consisting of accounts receivable turnover ratio, average age of accounts receivable, inventory turnover, average number of days inventory turnover in stock and the turnover of total assets is not enough therefore company management needs to improve the ability to manage its assets, inventories and receivables